Native multi-trait rhizobacteria promote growth and suppress foot rot in black pepper - K P Subila, Y K Bini, R Aravind, R Dinesh, M Anandaraj, A Kumar, (Journal of Spices and Aromatic Crops, 2014)
In this study, 74 PGPR isolates from different varieties of black pepper were characterized for morphological, biochemical and nutrient mobilization traits as well as inhibition of Phytophthora capsici (causing foot rot) under in vitro conditions. Based on the multiple traits, two PGPR [(Micrococcus luteus Schroeter (1872) Cohn 1872 (BRB3) and Enterobacter aerogenes Hormaeche and Edwards 1960 (AL) (BRB13)] were shortlisted for further growth promotion studies. For biocontrol studies, three PGPR [(Burkholderia cepacia (Palleroni & Holmes 1981) Yabuuchi et al. (1993) (BRB21), Pseudomonas aeruginosa Schröter (1872) Migula 1900 (BRB28) and Serratia marcescens Bizio 1823 (AL) (BRB49)] which showed >70% inhibition of P. capsici were shortlisted. The results from green house study on growth promotion indicated that application of M. luteus (BRB3) + 75% recommended dose (RD) of N + 100% RD of PK produced taller plants, longer roots, greater fresh biomass, more number of leaves and nodes in black pepper. This suggested a 25% reduction in chemical N fertilizer in the presence of M. luteus (BRB3). In the green house study on biocontrol, lowest foot rot (32.77%) and taller plants (332.0 cm) were observed with B. cepacia (BRB 21), which was on par with chemical treatment. This is the first report on the potential of PGPR like M. luteus for growth promotion and B. cepacia for management of P. capsici in black pepper.